Pendekatan Pemikiran Ekonomi Islam Muhammad Nejatullah Siddiqi - Rizal Darwis; Zulaeha Zulaeha (Al-Buhuts, 2022)
This paper aims to examine the thoughts of Muhammad Nejatullah Siddiqi regarding Islamic economics. The approach used in this paper is the qualitative approach. The data were collected from library data, both from primary and secondary sources. Furthermore, the data is analyzed and researched from general data, then specific conclusions are drawn using inductive, deductive, and descriptive data analysis techniques. The results of the study indicate that Siddiqi believes that fulfilling the needs of Muslims should be guided by Islamic law. One's success is closely related to moral values that are carried out using the Quranic paradigm